2018
DOI: 10.7717/peerj.6134
|View full text |Cite
|
Sign up to set email alerts
|

Shell variability in the stem turtlesProterochersisspp.

Abstract: BackgroundTurtle shells tend to exhibit frequent and substantial variability, both in bone and scute layout. Aside from secondary changes, caused by diseases, parasites, and trauma, this variability appears to be inherent and result from stochastic or externally induced flaws of developmental programs. It is, thus, expected to be present in fossil turtle species at least as prominently, as in modern populations. Descriptions of variability and ontogeny are, however, rare for fossil turtles, mainly due to rarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 64 publications
4
29
0
Order By: Relevance
“…Thus, these midsagittal ridges progressively decrease as ontogeny progresses, being absent in the mature stage. In fact, minor modifications in the carapace ornamentation pattern comparable with those recognized here for P. bullockii have been recognized as resulting from the ontogenetic variation in several species of extinct and extant turtles (Hay, 1908;Zangerl, 1953;de Broin, 1977;Somers et al, 2000;Danilov and Parham, 2008;Jansen and Klein, 2014;Cadena, 2015;Szczygielski et al, 2018).…”
Section: Qualitative Approachsupporting
confidence: 65%
See 2 more Smart Citations
“…Thus, these midsagittal ridges progressively decrease as ontogeny progresses, being absent in the mature stage. In fact, minor modifications in the carapace ornamentation pattern comparable with those recognized here for P. bullockii have been recognized as resulting from the ontogenetic variation in several species of extinct and extant turtles (Hay, 1908;Zangerl, 1953;de Broin, 1977;Somers et al, 2000;Danilov and Parham, 2008;Jansen and Klein, 2014;Cadena, 2015;Szczygielski et al, 2018).…”
Section: Qualitative Approachsupporting
confidence: 65%
“…As previously observed among representatives of other turtle groups (e.g. Sinemydidae, Proterochersidae or Baenidae; Shao et al, 2017;Smith et al, 2017;Szczygielski et al, 2018;Li et al, 2019), in shell elements that are ontogenetically dependent, the magnitude of shape change, as well as the growth rate, varies at the specific level. Therefore, in general, the ontogenetic development of P. bullockii is not shared with that known for any other pleurosternid.…”
Section: Comparison Of the Ontogenetic Development Ofsupporting
confidence: 56%
See 1 more Smart Citation
“…Among turtles, ontogenetic changes in fossils have been documented in Mesozoic and Cenozoic taxa, including modifications of the anterior scutes of the carapace in Proterochesis spp. ( Szczygielski et al., 2018 ); progressive skull stretching and enlargement of posterior and lateral emargination in the Late Cretaceous Bauremys elegans from Brazil ( Mariani and Romano 2017 ); and reduction of keels in the neural series of the Eocene Neochelys franzeni from Germany ( Cadena 2015 ). None of these taxa represent giant turtles (the largest-bodied species in their ecological category or clade, following Vermeij, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Turtles exhibit a wide assemblage of sexually dimorphic characters that can manifest through sexual shape dimorphism (Kuchling, 1997;Pritchard, 2008;Bonnet et al, 2010) or sexual size dimorphism (the most studied form of dimorphism between the sexes; Leuteritz & Gantz, 2013;Regis & Meik, 2017). For the extinct forms, only a few of these sexually dimorphic characters are available (Bonnet et al, 2010;Cadena et al, 2013;Limaverde et al, 2020;Szczygielski et al, 2018), which considerably complicates the evaluation of their sexual dimorphism. In this study, the quantitative approach demonstrated an evident sexual shape dimorphism in the morphology of the anal notch of Dortoka vasconica, the two sexual morphotypes previously observed by Pérez- being characterized.…”
Section: Discussion Sexual Shape Dimorphism In Extinct and Extant Pan-pleurodiresmentioning
confidence: 99%